PENGARUH KELEKATAN DAN POLA ASUH ORANG TUA TERHADAP KEMANDIRIAN SISWA DI SMP NEGERI KECAMATAN KEBASEN - SUSIYANTI, IIN (Universitas PGRI Semarang, 2023)
This research is motivated by low student independence, based on the pre-survey due to attachment factors and parenting patterns. Currently around many children are teenagers but do not have independence. This study aims to determine and prove the attachment and parenting patterns of parents towards independence. This type of research is ex post facto quantitative with a correlational research design. The population is Kebasen District Public Middle School students, totaling 1,873 students with a sample of 319 students. Proportionate Stratified Random Sampling technique. Collecting data on the scale of independence, attachment scale and parenting style using the Likert scale model. The results of multiple regression analysis between attachment and parenting patterns of parents on student independence in public junior high schools in Kebasen District have a significant effect with a percentage of 31.7%. Based on this research, counseling teachers can provide services to increase students' attachment and independence, especially in parenting parents who have a low category.